Transglutaminase 2 expression is enhanced synergistically by interferon-γ and tumour necrosis factor-α in human small intestine - Bayardo, Mariela Paula (2012)
Transglutaminase 2 (TG2) is expressed ubiquitously, has multiple physiological functions and has also been associated with inflammatory diseases, neurodegenerative disorders, autoimmunity and cancer. In particular, TG2 is expressed in small intestine mucosa where it is up-regulated in active coeliac disease (CD). The aim of this work was to investigate the induction of TG2 expression by proinflammatory cytokines [interleukin (IL)-1, IL-6, tumour necrosis factor (TNF)-α, interferon (IFN)-γ and IL-15] and the signalling pathways involved, in human epithelial and monocytic cells and in intestinal tissue from controls and untreated CD patients. Here we report that IFN-γ was the most potent inducer of TG2 expression in the small intestinal mucosa and in four [Caco-2, HT-29, Calu-6 and human acute monocytic leukaemia cell line (THP-1)] of five cell lines tested. The combination of TNF-α and IFN-γ produced a strong synergistic effect. The use of selective inhibitors of signalling pathways revealed that induction of TG2 by IFN-γ was mediated by phosphoinositide 3-kinase (PI3K), while c-Jun N-terminal kinase (JNK) and p38 mitogen-activated protein kinase (MAPK) were required for TNF-α activation. Quantitative polymerase chain reaction (PCR), flow cytometry and Western blot analysis showed that TG2 expression was blocked completely when stimulation by either TNF-α or IFN-γ was performed in the presence of nuclear factor (NF)-κB inhibitors (sulphasalazine and BAY-117082). TG2 was up-regulated substantially by TNF-α and IFN-γ in intestinal mucosa in untreated CD compared with controls. This study shows that IFN-γ, a dominant cytokine in intestinal mucosa in active CD, is the most potent inducer of TG2, and synergism with TNF-α may contribute to exacerbate the pathogenic mechanism of CD. Selective inhibition of signalling pathways may be of therapeutic benefit.